Poverty, Demographic Characteristics, and Public Policy in Cis Countries - Ahmad, Ehtisham (IMF Working Papers; Working Paper ;, 1993)
The demographic characteristics of different regions in the former Soviet Union influence the nature of poverty in the newly successor independent states of the FSU. Despite a common policy inheritance, major adjustments are needed in the major social protection instruments to reflect differences in demographics along with a changing resource base.